2013
DOI: 10.1002/jgrd.50468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ECMWF's soil moisture analyses using observations on the Tibetan Plateau

Abstract: An analysis is carried out for two hydrologically contrasting but thermodynamically similar areas on the Tibetan Plateau, to evaluate soil moisture analysis based on the European Centre for Medium‐Range Weather Forecasts (ECMWF) previous optimum interpolation scheme and the current point‐wise extended Kalman filter scheme. To implement the analysis, this study used two regional soil moisture and soil temperature networks (i.e., Naqu and Maqu) on the Tibetan Plateau. For the cold‐semiarid Naqu area, both ECMWF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 49 publications
8
133
0
Order By: Relevance
“…The ERA-Interim SM product will be adopted as the reanalysis data for this study [12]. The 12-month in situ data is deemed appropriate to capture the seasonal statistical moments, by using CDF matching technique [39,42].…”
Section: Flowchartmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERA-Interim SM product will be adopted as the reanalysis data for this study [12]. The 12-month in situ data is deemed appropriate to capture the seasonal statistical moments, by using CDF matching technique [39,42].…”
Section: Flowchartmentioning
confidence: 99%
“…A detailed quantification can facilitate identifying imperfections in the current numerical weather prediction models and may serve as a reference to which climate scenarios can be compared. Soil moisture (hereafter as SM) is a crucial land surface state that modulates land-atmosphere interactions [5][6][7][8][9][10] and imperative for quantifying trends and variability of feedbacks between climate and the water cycle of TP [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Soil moisture is one of the essential climate variables (ECVs) [1][2][3][4]. On land, soil moisture is one of the few variables depicting the storage of water and heat that can be released several months later, as vegetation cover and snow do [5][6][7].…”
Section: Motivationmentioning
confidence: 99%
“…T B " εT e f f (1) where T B is the radiation intensity received by the passive microwave sensor fixed near the soil surface or on the satellite platforms while neglecting the attenuation of atmosphere. ε is the emissivity that is strongly related to soil moisture.…”
Section: Introductionmentioning
confidence: 99%
“…The use of TERA leads to a general underestimation of the brightness temperature throughout the entire season. Indeed, Su et al (2013) found that in the Maqu area, as well as other parts of the Tibetan Plateau, ECMWF model underestimates the soil temperature.…”
Section: Final Remarks and Recommendationsmentioning
confidence: 99%